Effect of the hydrogen sulfide donor GYY4137 on platelet activation and microvascular thrombus formation in mice. (May 2014) - Grambow, Eberhard; Mueller-Graf, Fabian; Delyagina, Evgenya; Frank, Marcus; Kuhla, Angela; Vollmar, Brigitte
Abstract This study evaluates the effect of the H2S donor GYY4137 (GYY) on adhesion molecule expression, protein S-sulfhydration and morphology of platelets in vitro and on kinetics of microvascular thrombus formation in vivo. Using flowcytometry, untreated resting, TRAP-activated, or TRAP-activated and GYY-exposed human platelets were studied for expression of P-selectin, GPIb and GPIIb/IIIa as well as for fibrinogen binding. By means of electron microscopy, platelet morphology and intracellular granule numbers were assessed. Platelet shape change was studied using immunohistochemistry for P-selectin, NSF and F-actin by SR-SIM. Biotin switch assay served for the analysis of platelet protein S-sulfhydration by GYY. Using the FeCl3 and the light/dye model in dorsal skinfold chamber-equipped mice, the effect of GYY and its vehicle DMSO was studied on venular thrombus formation and tail-vein bleeding time. Soluble (s)P-selectin plasma concentrations were measured in GYY- or DMSO-treated animals. Exposure to GYY increased the S-sulfhydration of platelet proteins. GYY reduced dose-dependently the TRAP-induced adhesion molecule expression and attenuated the morphological signs of TRAP-associated platelet activation. In mice, GYY caused a significant prolongation of venular thrombus formation and tail-vein bleeding time. Application of an anti-P-selectin antibody in DMSO-exposed animals prolonged thrombosis formation comparably as GYY did. GYY reversed the TRAP-induced distribution of P-selectin at the plasma membrane of platelets. This indicates reduced exocytosis and shedding of P-selectin, which is supported by significantly lower sP-selectin concentrations in GYY- vs. DMSO-treated mice. H2S acts anti-thrombotic and seems to regulate thrombogenesis by interference with platelet activation and adhesion molecule-mediated aggregation.